INTERFACE PRESCRIBING ISSUES AT ST GEORGE'S TIC DISORDER CLINIC. Issue 9 (13th August 2015) - Emberton, John; Stern, Jeremy
Abstract : Objective: This study attempted to quantify and analyse the prescribing issues experienced by patients of the St George's tic disorder clinic since 2005 and highlight any particular problem areas which could be improved in the hope of improving prescribing practices for the future. Drugs given for Tourette syndrome (TS) are frequently unlicensed or off-label for the condition and in some cases not licensed for use in children at all. Pharmaceutical companies have not yet applied for marketing licences for the condition. This can cause problems in the transfer of prescribing from specialist to primary care (family medicine, general practice) due to unfamiliarity of non-specialists with the drugs even where continued usage appears safe and unproblematic. The two most relevant drugs in the UK were felt to be aripiprazole and melatonin. For this reason the study prioritised the data concerning the continuation of these drugs by including patients prescribed one or the other who had a diagnosis of Tourettes syndrome. A further inclusion criterion was the refusal of any other drug. Method: We reviewed a sample of 500 patients' notes both adult and paediatric – from the clinic in order to collect raw data. Any issues in the transfer of their prescriptions were recorded as well as patient age, year of prescription and the primary care trust to which the GP practice belonged. In addition to this, the clinical outcome of any included patient was qualified to determine the consequence of any prescribing issues. Results: In brief, results based on location of a GP practice and the year in which the prescription was requested were unremarkable. The study showed that GPs refuse to prescribe aripiprazole far more than any other medication for the treatment of Tourette syndrome (13 out of 19 drug refusals in the sample) and refused to continue 8.6% of all aripiprazole prescriptions made by the clinic. Of the SE 13 incidents where a prescription of aripiprazole was not continued, 8 were adults (11% of all adults prescribed aripiprazole) and 5 were children (6.3% of all children prescribed aripiprazole). Of these 13 patients: 3 eventually received no prescription while 2 were prescribed alternatives to aripiprazole. Conclusion: Transfer of prescribing to primary care of a currently widely used drug for tics in the UK has been problematic in a small minority of cases.